Glucohealth: The potential of porang (Amorphophallus muelleri) acid hydrolysed glucomannan as an inhibitor of SARS-CoV-2 interaction with ACE2 - Amira Hasnanuha Ulayya; Ahmad Zaki Mubarok; Widodo Widodo; Simon Bambang Widjanarko; Marlita Eklesia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
The novel SARS-CoV-2 that causing global pandemic COVID-19 known to enter the host cell using the hACE2 as cell receptor. SARS-CoV S1 protein cleaves the ACE2 receptor, then the S2 subunits facilitates the cell membrane fusion, the inhibition of S1-ACE2 interaction can help develop anti SARS-CoV-2 medication. Porang glucomannan is a polysaccharide known as immunomodulator but never reported as anti-virus by direct inhibition of viral entry. Glucohealth was developed to investigate its potential. Method: Glucohealth is a glucomannan hydrolysate (HGM) that made from porang (Amorphophallus muelleri). Hydrolysis was carried using HCl in different concentration (0.25N, 0.5N, 1N) then analyzed its inhibitor activity using ELISA kit. Result: Higher HCl concentration produced HGM with smaller average particle size and lower glucomannan content. However, ELISA studies showed that glucomannan, including its hydrolysates, have the potency to bind with S1 protein and inhibit the binding activity of S1-ACE2. Degraded glucomannan proven to have better bioactivity and able to interact with pathogen to inhibit its cell entry. This project should be a gateway for further biomedical study of glucomannan from Indonesia’s local tuber and new approach to produce more natural therapy against COVID-19.